2022
DOI: 10.18502/ijph.v51i11.11163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Deprivation on Hospitalization and Intensive Care Unit Admission among COVID-19 Patients: A Systematic Review and Meta-Analysis

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has disproportionately affected socially disadvantaged groups; however, the association between socioeconomic status and healthcare utilization among COVID-19 patients remains unclear. Therefore, a systematic review and meta-analysis was conducted to assess the association between socioeconomic status and hospitalization and intensive care unit admission among COVID-19 patients. Methods: PubMed, Embase, and the Cochrane Register of Controlled T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Similarly, other studies have found higher hospitalization rates in the most deprived areas of the USA, UK, and France [43][44][45][46] and a small meta-analysis [47] assessing the influence of deprivation on the risk of hospital admission.…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, other studies have found higher hospitalization rates in the most deprived areas of the USA, UK, and France [43][44][45][46] and a small meta-analysis [47] assessing the influence of deprivation on the risk of hospital admission.…”
Section: Discussionmentioning
confidence: 71%
“…Coronavirus Disease 2019 profoundly impacted the health-care environment, economy, and society. 9 , 10 In this large retrospective cohort study, we demonstrated that the proportion of patients diagnosed with stage 4 pancreatic cancer in a population where surgery is challenging was higher in the COVID-19 period than in the pre-COVID-19 period. This finding suggests that delays in the detection of pancreatic cancer during the COVID-19 pandemic may have existed, leading to a higher proportion of patients presenting with more advanced disease stages.…”
Section: Discussionmentioning
confidence: 84%